MILLENNIAL GENERATION POLITICAL COMMUNICATION STYLE: GIBRAN RAKABUMING RAKA CASE STUDY - Andi Budi Sulistijanto (Jurnal Visi Komunikasi, 2026)
The abstract encapsulates the essence of the research on the Millennial Generation's political communication style, with a focus on Gibran Rakabuming Raka as a pivotal case study. This research aims to bridge the gap in understanding the long-term impact of millennial political communication on Indonesia's social and political landscape. Utilizing qualitative analysis of interviews, social media, news, and scholarly publications, this study delves into Gibran's innovative communication strategies and their resonance with the millennial demographic. The findings suggest that Gibran's approach, characterized by digital savviness and an authentic engagement style, significantly influences millennial political participation and civic engagement. This shift towards a more inclusive and transparent political discourse reflects broader changes in political communication practices, aligning with the preferences of a generation that values direct interaction and genuine representation. The study underscores the challenges of adapting traditional political communication to the digital era, emphasizing the need for political figures to navigate these complexities with strategic innovation and ethical consideration. The implications of this research extend to future political engagement strategies, highlighting the critical role of digital platforms in shaping political discourse and fostering meaningful engagement with the millennial generation. This research contributes to the broader discourse on political communication, offering insights into the evolving landscape of political engagement and the pivotal role of millennials in shaping Indonesia's political future.